2010
DOI: 10.1074/jbc.m109.024703
|View full text |Cite
|
Sign up to set email alerts
|

Kidins220/ARMS Modulates the Activity of Microtubule-regulating Proteins and Controls Neuronal Polarity and Development

Abstract: In order for neurons to perform their function, they must establish a highly polarized morphology characterized, in most of the cases, by a single axon and multiple dendrites. Herein we find that the evolutionarily conserved protein Kidins220 (kinase D-interacting substrate of 220-kDa), also known as ARMS (ankyrin repeat-rich membrane spanning), a downstream effector of protein kinase D and neurotrophin and ephrin receptors, regulates the establishment of neuronal polarity and development of dendrites. Kidins2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 96 publications
4
55
0
Order By: Relevance
“…Since most hippocampal neurons expressing Kidins220 1-402 did not bear neurites after 1 day in vitro, it is likely that the ankyrin repeats affects neurite initiation, which is important for both dendritic and axonal growth. This is in accordance with previous studies, which showed that Kidins220 regulates dendritic branching in vivo (Wu et al, 2009), and modulated the development of both axons and dendrites (Higuero et al, 2009). In summary, this experiment demonstrates that the inhibitory activity of the ankyrin-rich domain of Kidins220 on neurite outgrowth also occurs in hippocampal neurons, strongly suggesting that the pathway elucidated in PC12 cells has general validity and controls differentiation in primary neurons.…”
Section: The N-terminus Of Kidins220 Inhibits Neurite Outgrowth In Prsupporting
confidence: 82%
“…Since most hippocampal neurons expressing Kidins220 1-402 did not bear neurites after 1 day in vitro, it is likely that the ankyrin repeats affects neurite initiation, which is important for both dendritic and axonal growth. This is in accordance with previous studies, which showed that Kidins220 regulates dendritic branching in vivo (Wu et al, 2009), and modulated the development of both axons and dendrites (Higuero et al, 2009). In summary, this experiment demonstrates that the inhibitory activity of the ankyrin-rich domain of Kidins220 on neurite outgrowth also occurs in hippocampal neurons, strongly suggesting that the pathway elucidated in PC12 cells has general validity and controls differentiation in primary neurons.…”
Section: The N-terminus Of Kidins220 Inhibits Neurite Outgrowth In Prsupporting
confidence: 82%
“…PKD1 phosphorylates the scaffold protein Kidins220 [55][56][57][58] . Kidins220 transportation from the TGN to the plasma membrane requires the autophosphorylation of PKD1 at Ser916.…”
Section: Role Of Pkd In Neuronal Polaritymentioning
confidence: 99%
“…Kinase D-interacting substrate of 220 kDa (Kidins220), also known as ankyrin repeat-rich membrane spanning (ARMS), is a protein expressed predominantly in neural tissues. Kidins220 is the fi rst known physiological substrate of protein kinase D (PKD) and has been shown to have a role in determining neuronal polarity (Higuero et al, 2010). Calpain proteolysis infl uences Kidins220 functions and thus may also infl uence neuronal polarity via the PKD pathway (Lopez-Menendez et al, 2009).…”
Section: Role Of Protein Degradation In the Establishment Of Neuronalmentioning
confidence: 99%